ASAP1 regulates the uptake of Mycobacterium tuberculosis H37Ra in THP1-derived macrophages by remodeling actin cytoskeleton. (July 2021) - Cui, Jia; Chen, Guangxin; Zhao, Zhonghua; Wang, Liqing; Wen, Da; Xing, Li; Wu, Changxin
Abstract: Tuberculosis is initiated by the entry of Mycobacterium tuberculosis (Mtb) into macrophages in the lungs. A study of the cellular factors responsible for the entry of Mtb into host cells will potentially benefit the development of therapeutic treatments or preventive agents against Mtb infection. Using human THP1-derived macrophages as a model, we found that infection of Mtb H37Ra transiently reduced the level of ASAP1, an ADP ribosylation factor (Arf)-GTPase activating protein. Furthermore, knockdown of ASAP1 increased the efficiency of H37Ra entry into the cell and altered the status of actin remodeling as indicated by the enhanced aggregation of F-actin and the increased numbers of vinculin- and paxillin-rich puncta. Collectively, the results in this report identified ASAP1 as a regulator controlling the entry of Mtb H37Ra into macrophage by remodeling actin cytoskeleton. Highlights: Mtb H37Ra infection reduces ASAP1 in THP1-derived macrophage. Knockdown of ASAP1 increases the efficiency of Mtb H37Ra entry into the cell. Knockdown of ASAP1 alters actin remodeling. ASAP1 regulates the entry of Mtb H37Ra into macrophage.